Seeing the forest through the palms: developments in environmentally sustainable palm oil production and zero-deforestation efforts - Ostfeld, Rosemary; Reiner, David M. (Frontiers in Sustainable Food Systems, 2024)
Palm oil is produced on plantations primarily in Indonesia and Malaysia, which, historically, have been responsible for significant tropical deforestation and ecosystem loss. Driven by a shift away from hydrogenated vegetable oils and its high productivity, palm oil is now part of more than half of all packaged consumer products. Given its centrality across many supply chains, certification schemes have sought to improve environmental sustainability in the palm oil industry. Increasingly, there is an intersection between certification schemes and regulatory drivers. The recent 2023 European Union regulation on deforestation-free products aims has implications for palm oil and many other forest products. Environmental certification schemes, such as the one developed by the Roundtable on Sustainable Palm Oil, have the potential to play a critical role in the implementation of this recent policy for palm oil and can serve as model for many other commodities subject to the new Directive.